Study MaterialsCBSE NotesSolving Algebraic Fractions | Simplify & Reduce Algebraic Fractions

Solving Algebraic Fractions | Simplify & Reduce Algebraic Fractions

Find the solved example questions on algebraic fractions. This article includes addition, subtraction, multiplication, division, simplification, and reducing a fraction to its lowest term. By reading this page, you can solve any type of algebraic fraction questions easily & quickly. So, have a look at all the questions and solutions provided below and learn the concepts involved easily.

Questions on Solving Algebraic Fractions

Example 1.

    Fill Out the Form for Expert Academic Guidance!



    +91


    Live ClassesBooksTest SeriesSelf Learning




    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Simplify the algebraic fraction [1 + 1 / (x + 1)] / [x – 4/x]?

    Solution:

    Given fraction is [1 + 1 / (x + 1)] / [x – 4/x]

    Find the L.C.M of denominators.

    [(1. (x + 1)+ 1) / (x + 1)] / [(x² – 4) / x]

    = [(x + 2) / (x + 1)] / [(x² – 2²) / x]

    = [(x + 2) / (x + 1)] * [x / (x + 2) (x – 2)]

    = [x(x + 2)] / [(x + 1) ( x – 2) (x + 2)]

    = x / [(x + 1) (x – 2)]

    ∴[1 + 1 / (x + 1)] / [x – 4/x] = x / [(x + 1) (x – 2)]

    Example 2.

    Simplify the algebraic fraction [((k² + 1 / k – 1) – k) / ((k² – 1 / k + 1) + 1)] [1 – 2/(1 + 1/k)]?

    Solution:

    Given algebraic fraction is [((k² + 1 / k – 1) – k) / ((k² – 1 / k + 1) + 1)] [1 – 2/(1 + 1/k)]

    Find the L.C.M of denominators of the first fraction and simplify.

    = [(k² + 1 – k (k – 1)) / (k – 1)] / [(k² – 1 + 1 (k + 1)) / (k + 1)]

    = [(k² + 1 – k² + k)) / (k – 1)] / [(k² – 1 + k + 1)) / (k + 1)]

    = [(k + 1) / (k – 1)] / [(k² + k) / (k + 1)]

    = [(k + 1) / (k – 1)] / [(k(k + 1) / (k + 1)]

    = [(k + 1) / (k – 1)] / k / 1

    = (k + 1) / k(k – 1)

    = (k + 1) / (k² – 1²)

    = (k + 1) / (k + 1) ( k – 1)

    = 1 / (k – 1)

    Simplification of the second fraction is

    [1 – 2/(1 + 1/k)]= [1- 2 / k(k +1)]

    = [k(k +1) – 2] / [k(k +1)]

    = (k² + k – 2) / [k(k +1)]

    = (k² + 2k – k – 2) / (k(k +1))

    = (k (k + 2) – 1(k + 2)) / (k(k +1))

    = [(k – 1) ( k + 2)] / (k(k +1))

    Product of first and second fraction is

    = 1 / (k – 1) * [(k – 1) ( k + 2)] / (k(k +1))

    = (k + 2) / k(k +1)

    ∴ [((k² + 1 / k – 1) – k) / ((k² – 1 / k + 1) + 1)] [1 – 2/(1 + 1/k)] = (k + 2) / k(k +1)

    Example 3.

    Reduce the algebraic fractions [3 / √(1+x) + √(1-x)] : [3 / √(1 – x²) + 1]

    Solution:

    Given algebraic fraction is [3 / √(1+x) + √(1-x)] : [3 / √(1 – x²) + 1]

    Simplification of first fraction is

    3 / √(1 + x) + √(1 – x)

    = (3 + √(1 + x) * √(1 – x)) / √(1 + x)

    = (3 + √(1 + x)(1 – x) / √(1 + x)

    Simplification of the second fraction is

    3 / √(1 – x²) + 1

    = 3 + √(1 – x²) / √(1 – x²)

    The division of algebraic fraction is

    = [(3 + √(1 + x)(1 – x) / √(1 + x)] : [3 + √(1 – x²) / √(1 – x²)]

    = [(3 + √(1 + x)(1 – x) (√(1 – x²))] / [√(1 + x) (3 + √(1 – x²))

    = √(1 – x²) / √(1 + x)

    = √(1 + x)(1 – x) / √(1 + x)

    = √(1 – x)

    ∴ [3 / √(1+x) + √(1-x)] : [3 / √(1 – x²) + 1] = √(1 – x)

    Example 4.

    Reduce to lowest terms — if possible 3x / 4a²b – 7 / 6ab⁵ – 5x / 2ab².

    Solution:

    Given fraction is 3x / 4a²b – 7 / 6ab⁵ – 5x / 2ab²

    Find the L.C.M of all terms denominators.

    L.C.M of 4a²b, 6ab⁵, 2ab² is 12a²b⁶.

    = [3x . 3b⁵]/12a²b⁶ – [7 . 2a]/12a²b⁶ – [5x . 6ab⁴]/12a²b⁶

    = [9xb⁵ – 14a – 30xab⁴]/ 12a²b⁶

    ∴ 3x / 4a²b – 7 / 6ab⁵ – 5x / 2ab² = [9xb⁵ – 14a – 30xab⁴]/ 12a²b⁶

    Chat on WhatsApp Call Infinity Learn

      Talk to our academic expert!



      +91


      Live ClassesBooksTest SeriesSelf Learning




      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.